PENERAPAN METODE TALKING STICK UNTUK PENINGKATAN PEMAHAMAN KONSEP MATEMATIKA SISWA SMP NEGERI 5 KUNINGAN - Santi Sridamayanti; Muhammad Irfan Habibi; Zuli Nuraeni (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2016)
This research is an experimental class and control class all aimed to determine students who obtain learning through talking stick method is better than the expository method in an increased understanding of mathematical concepts and there is an increased understanding of mathematical concepts using talking stick method. Penenlitian design is pretest-posttest control group desigen which is one type of True Experimental design. The population in this study were students of class VIII SMP Negeri 5 Kuningan in the school year 2015/2016 as many as 103 were distributed in three classes. Samples were students of class VIII A and VIII B were taken by simple random sampling. Data is the value of understanding mathematical concepts derived from the test results. Based on test data hypothesis that students who acquire learning through talking stick method is better than the expository method in an increased understanding of mathematical concepts and there is an increased understanding of mathematical concepts using talking stick method. Thus, it can be concluded that the application of the talking stick method can improve students' understanding ofmathematical concepts SMP Negeri 5 Kuningan.